1996
DOI: 10.1128/iai.64.8.3210-3217.1996
|View full text |Cite
|
Sign up to set email alerts
|

The (alpha2-->8)-linked polysialic acid capsule of group B Neisseria meningitidis modifies multiple steps during interaction with human macrophages

Abstract: Group B Neisseria meningitidis causes systemic disease, including meningitis, after initial colonization and subsequent penetration of nasopharyngeal mucosa, a tissue which is richly populated by macrophages. In an initial effort to characterize the interaction of N. meningitidis and mature human macrophages, the influence of the (␣238)-linked polysialic acid capsule on the interaction of N. meningitidis with human monocyte-derived macrophages was investigated with a capsulate case isolate and an isogenic Tn91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 32 publications
1
21
0
1
Order By: Relevance
“…We successfully isolated primary human PMNs (demonstrated by their expression of surface markers including CD68, CD11b, CD18 and CEACAMs, and neutrophil elastase), and showed the anti-phagocytic effect of the polysaccharide capsule of N. meningitidis as demonstrated previously (Read et al, 1996;Unkmeir et al, 2002). Interestingly, our assays showed that, compared with E. coli and S. flexneri, wild-type N. meningitidis exhibits enhanced survival when in association with PMNs as does N. gonorrhoeae (Veale et al, 1979).…”
Section: Discussionsupporting
confidence: 65%
“…We successfully isolated primary human PMNs (demonstrated by their expression of surface markers including CD68, CD11b, CD18 and CEACAMs, and neutrophil elastase), and showed the anti-phagocytic effect of the polysaccharide capsule of N. meningitidis as demonstrated previously (Read et al, 1996;Unkmeir et al, 2002). Interestingly, our assays showed that, compared with E. coli and S. flexneri, wild-type N. meningitidis exhibits enhanced survival when in association with PMNs as does N. gonorrhoeae (Veale et al, 1979).…”
Section: Discussionsupporting
confidence: 65%
“…Down-modulation of meningococcal OMP-mediated adherence by surface sialic acids has been frequently observed (Stephens et al, 1993;Virji et al, 1995a;Read et al, 1996;McNeil and Virji, 1997;Hardy et al, 2000). As adhesins such as Opa and Opc are integral OMPs located beneath the capsule, one obvious explanation for such down-modulation is steric hindrance/physical masking by the polysaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies and those of others have shown that under the influence of invasins, meningococci lacking capsule invade target cells more readily than fully capsulate bacteria (Virji et al, 1993;Read et al, 1996;Deghmane et al, 2000;Hardy et al, 2000). As capsule is subject to natural phase variation and capsule expression may also be controlled by environmental conditions or signals from target cells (Masson and Holbein, 1985;Deghmane et al, 2002), we assessed the internalized phenotype with respect to the expression of capsule and other major surface factors.…”
Section: Internalized #1818 Retain Demonstrable Levels Of Capsule Anmentioning
confidence: 99%